1997
DOI: 10.1039/a701686g
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Heavy Metals at Picogram per Gram Levels in Greenland and Antarctic Snow by Double Focusing Inductively Coupled Plasma Mass Spectrometry

Abstract: The potential of a double focusing ICP-MS instrument in of sample contamination during collection, storage, treatment terms of high sensitivity, sample throughput and low volume of and analysis. As an example, the very few reliable data sets sample consumed was investigated for the direct, simultaneous available for Cd, Pb, Zn and Cu show that their concentrations determination of Co, Cu, Zn, Mo, Pd, Ag, Cd, Sb, Pt, Pb, Bi range from tenths of pg g−1 (10−12 g g−1) in Antarctic and U at the low and sub-pg g−1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 29 publications
1
64
0
3
Order By: Relevance
“…In some cases, such as those studies in the Antarctic and Greenland, filtering is simply not possible due to the extremely low abundance of elements, and it is therefore assumed that any particulate matter is incorporated during analysis. This seems a reasonable assumption for more recent analytical methods such as laser-excited atomic fluorescence spectrometry (Bolshov and Boutron, 1994;Bolshov et al, 1997) or sector-ICP-MS ( Barbante et al, 1997;Townsend and Edwards, 1998). However, for studies of snowpack in areas that are not permanently snow-covered and those that receive large amounts of pollution, particulates are the dominant source of the chemical load for many elements and especially for many trace elements (Table 1 this paper; Gregurek et al, 1999a;Gregurek et al, 1999b;Caritat et al, 1998;Reimann, 1998;Gregurek et al, 1998;Reimann et al, 1996).…”
Section: Comparison To Other Studiesmentioning
confidence: 93%
“…In some cases, such as those studies in the Antarctic and Greenland, filtering is simply not possible due to the extremely low abundance of elements, and it is therefore assumed that any particulate matter is incorporated during analysis. This seems a reasonable assumption for more recent analytical methods such as laser-excited atomic fluorescence spectrometry (Bolshov and Boutron, 1994;Bolshov et al, 1997) or sector-ICP-MS ( Barbante et al, 1997;Townsend and Edwards, 1998). However, for studies of snowpack in areas that are not permanently snow-covered and those that receive large amounts of pollution, particulates are the dominant source of the chemical load for many elements and especially for many trace elements (Table 1 this paper; Gregurek et al, 1999a;Gregurek et al, 1999b;Caritat et al, 1998;Reimann, 1998;Gregurek et al, 1998;Reimann et al, 1996).…”
Section: Comparison To Other Studiesmentioning
confidence: 93%
“…This technique, thanks to the extremely low noise signal and the very high ion transmission, is very attractive for ultratrace determination in environmental matrices (26,27). In particular, it was recently demonstrated that snow and ice, due to the high purity of the matrix, are well suited for direct PGMs determination (21,22,28 as three times the standard deviation of the blanks, were 0.008, 0.08, and 0.02 pg/g for Pt, Pd, and Rh, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the accurate determination of trace elements in Antarctic surface snow was achieved (Barbante et al, 1997; http://dx.doi.org/10.1016/j.chemosphere.2014.10.094 0045-6535/Ó 2014 Elsevier Ltd. All rights reserved. Ikegawa et al, 1999;Dahe et al, 1999;Grotti et al, 2011;Thamban and Thakur, 2013).…”
Section: Introductionmentioning
confidence: 98%